2000
DOI: 10.1086/302865
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Locus (DFNA24) for Prelingual Nonprogressive Autosomal Dominant Nonsyndromic Hearing Loss Maps to 4q35-qter in a Large Swiss German Kindred

Abstract: Nonsyndromic hearing loss is one of the most genetically heterogeneous traits known. A total of 30 autosomal dominant nonsyndromic hearing-loss loci have been mapped, and 11 genes have been isolated. In the majority of cases, autosomal dominant nonsyndromic hearing loss is postlingual and progressive, with the exception of hearing impairment in families in which the impairment is linked to DFNA3, DFNA8/12, and DFNA24, the novel locus described in this report. DFNA24 was identified in a large Swiss German kindr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…The human caspase-3 gene has been mapped to chromosome 4q35 (25)(26)(27), a region that also contains the locus for DFNA24, an autosomal dominant, nonsyndromic form of hearing loss (27). Nonsyndromic hearing loss is one of the most genetically heterogeneous inherited traits known (39), with more than 60 loci having been mapped.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The human caspase-3 gene has been mapped to chromosome 4q35 (25)(26)(27), a region that also contains the locus for DFNA24, an autosomal dominant, nonsyndromic form of hearing loss (27). Nonsyndromic hearing loss is one of the most genetically heterogeneous inherited traits known (39), with more than 60 loci having been mapped.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we generated caspase-3 knockout mice and showed that these animals develop deafness with accompanying degeneration of spiral ganglion neurons and hair cells in the inner ear, suggesting that caspase-3 is required for the survival of ganglion cells and hair cells. Given that the human caspase-3 gene has been mapped to a chromosomal position close to that implicated in a form of nonsyndromic hearing loss (25)(26)(27), the caspase-3-deficient mice may represent a model for this congenital form of human deafness.…”
mentioning
confidence: 99%
“…In addition, linkage analysis has identified loci on chromosome 4q35 for several other disorders including benign intraepthelial dyskeratosis (DKBI), 20 Bietti crystalline corneoretinal dystrophy (BCD), 21 Buekes type hip dysplasia (BHD), 22 and prelingual nonprogressive autosomal dominant nonsyndromic hearing loss (DFNA24). 23 The transcript map presented in this study may also provide candidate genes for investigation in these disorders.…”
Section: Discussionmentioning
confidence: 91%
“…The genetic analysis for the family under study is reported elsewhere [Häfner et al, 2000]. A maximum multipoint LOD score of 11.6 was obtained at marker D4S1652.…”
Section: Methodsmentioning
confidence: 99%
“…The DFNA24 locus was first identified in a Swiss-German family with a history of autosomal dominant nonsyndromic HI which dates back to the mid-19th century [Häfner et al, 2000]. To date, the causative gene for this locus has not been identified, and no other family or pop-ulation has been linked to the same locus, inhibiting further fine-mapping efforts and validation of potential sequence variants.…”
Section: Introductionmentioning
confidence: 99%